IMPLEMENTASI PEMBELAJARAN IPS PADA ANAK-ANAK HOMESCHOOLING TINGKAT SMP (Studi Kasus Di Homeschooling Kak Seto (HSKS) Solo) - Nur Agustiningsih (Jurnal Ilmiah Dikdaya, 2017)
Abstract:  Homeschooling is one of informal education institutions the existence of which had gotten legality. Through typical learning method, Homeschooling could be an education alternative for parents and children reluctantly attending formal education. The objectives of research were to find out the Social Science learning plan in Kak Seto Homeschooling (HSKS) of Solo, to find out the assessment of Social Science learning in Kak Seto Homeschooling (HSKS) of Solo, and to find out the constraints of Social Science in Kak Seto Homeschooling (HSKS) of Solo. This study was a descriptive qualitative research with case study strategy. Techniques of collecting data employed were interview, observation, and document analysis. The sampling technique used was purposive sampling. The data validation was conducted using triangulation. Technique of analyzing data used was an interactive model of analysis encompassing data collection, data display and conclusion drawing. From the result of research, it could be concluded that 1) tutor implemented the learning plan by developing syllabus and RPP, 2) Social Science learning was conducted in community and distance learning methods; the procedure of learning was carried out in three stages: introduction, main activity and closing, but the tutor had not implemented each stage completely yet; the method used was varied but the tutor still dominated the learning course. 3) In the assessment process, tutor used formative assessment, summative assessment and portfolio; 4) The constraints found during learning process included tutor encountered difficulty during teaching the material beyond his/her discipline, tutor found difficultly the appropriate method to attract the student interest and motivation, the lack of time effectiveness in learning.Keywords: Homeschooling, Social Science Learning.